Bank of the United States (Baltimore, Md.) records - Bank of the United States (Baltimore, Md.)
Correspondence and banking and legal records documenting loans and other business of the Baltimore bank, both as a branch of the Bank of the United States and as a corporate state-chartered bank.
Congressionally-chartered as a branch of the Bank of the United States in 1792; continued under a charter from the State of New York after the charter of the Bank of the United States expired in 1811; chartered anew as the Baltimore branch of the second Bank of the United States in 1816; Merchants' Bank of Baltimore assumed the business of the Baltimore branch after the expiration of the charter of the Second Bank of the United States in 1836.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bank of the United States (1791-1811); Bank of the United States (1816-1836); Merchants' Bank of Baltimore (Baltimore, Md.); Bank loans -- Maryland -- Baltimore; Banks and banking -- Maryland -- Baltimore; Banks and banking -- United States